DETERMINANTS OF PROACTIVE CAREER BEHAVIOUR AMONG FEMALE WORKERS: PROACTIVE PERSONALITY AS A MODERATOR - Sin Yee Cheong; Cheng Ling Tan; Jian Ai Yeow; Chew Sze Cheah (International Journal of Accounting, Finance and Business, 2020)
Nowadays, the increasing trend of female labour force participation in Malaysia signifies a positive impact on Malaysia gross domestic product (GDP) which helps to boost the economy. Many companies begin to realise the significance of women in the organization as they will help to improve the quality of engagement and mutual understanding between organizations and the community. Nevertheless, the proactive career behaviour of women becomes more vital to be understood for encouraging and retaining women in the workplace. Female employees slowly become an important contributor to today's economy and yet, there is scare of researches on this related topic. In this, the researchers are motivated to study the determinants of proactive career behaviour among female employee. This study is based on 150 female employees who work in the private sectors in Peninsular Malaysia. The motivating factors include future work self, career adaptability, perceived career barriers, dispositional hope and proactive personality. The moderator role of proactive personality was also assessed in the model. Descriptive and inferential statistics are used to determine the relationship between those variables. In this research, the result has shown that future work self and proactive personality are significant influence the proactive career behaviour of female employees. Contrary to our expectation, there is insufficient evidence to support moderating effects in the study. This study contributes some implication to management to act to foster the proactive behaviour of female employees. Common method variance and generalisation issue due to small sample size are some of the limitations. Thus, some recommendation for future research were laid out in the study.